Michel Foucault: filósofo político - Sasso, Emanuel Dos Santos [UNIFESP] (2019)
The present work intends, through a historiographical procedure about the vast production of the French philosopher Michel Foucault, to instrumentalize ideas, notions and concepts developed by the thinker to try to understand the political problems of our time. To this end, we propose a reading that seeks not only to reinforce the idea of a Foucault strictly philosopher, but which, by considering it is an external reading of the great philosophical references, reveals the deepest links of the French philosopher with the field of politics. These bonds, as we shall see, go beyond circumstance. In making a foray into Michel Foucault's thinking, what we seek is to show that the Foucaultian 'toolbox' allows us to reflect on what would be the central question of philosophy - what are we about to become? - in the political sphere. Notwithstanding the complex methodology developed by Foucault and the strong diversity of his work, we intend to show that his thinking occupies today a strategic point in our political conjecture - whether it is theoretical, practical, local or international. What we intend, therefore, with the production of this thesis, is to bring to light all the diversity of discourse that can be mobilized by philosophy in the political sphere. In order to achieve this inference, we will seek to show what effects can be produced in the political sphere from the representation and, above all, from the understanding of the philosophical work developed by Michel Foucault.